ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH PROVINSI DI INDONESIA - Rosita Wulandari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to examine the effect of partially balanced funds, local tax revenues and regional expenditure on the financial performance of local governments in the Indonesian province. This study was conducted at the Directorate General of Fiscal Balance (DJPK) Ministry of Finance in the period 2012-2018 through the official website www.djpk.kemenkeu.go.id. Regional financial performance is measured using the ratio of fiscal decentralization by comparing the Original Regional Revenue and Total Revenue, while the balancing fund, Regional Tax Revenue and Regional expenditure are calculated based on each of the realization of these variables. The population used in this study is all provinces in Indonesia during the 2012-2018 period as many as 34 provinces. Sampling uses the Purposive Sampling method with the criteria of the provincial government which has an official website of the local government and which publishes the Budget Realization Report (LRA) so that a sample of 14 provinces is obtained over a 7-year period. The results showed that simultaneous balancing funds, local tax revenues, and regional spending affect the financial performance of provincial government in Indonesia. Whereas partially shows that regional tax revenue and regional expenditure affect the financial performance of the provincial government in Indonesia while the balance fund does not affect the financial performance of the provincial government in Indonesia. Future studies can develop the results of this study by adding other variables such as regional retribution, size and wealth, and can replace financial performance measurements with efficiency ratios or regional independence ratios